Identity work among girls with ADHD: struggling with Me and I, impression management, and social camouflaging in school - Grimell, Jan; Ericson, Maja; Frick, Matilda A. (Frontiers in Psychology, 2025)
The number of individuals diagnosed with ADHD is rapidly increasing in Sweden, with approximately two-thirds of diagnosed children being boys. However, among older adolescents, ADHD now appears to be more common among girls. Despite this, girls remain an understudied group. The purpose of this study was to explore how girls with ADHD described their identity work amid the tension between norms of socially appropriate female behavior (conceptualized as the Me) and their true selves (conceptualized as the I). Ten participants aged 15 to 18 years were included. A thematic inductive analysis was conducted, complemented by an abductive approach incorporating a dramaturgical perspective and the concepts of Me and I, impression management, and social camouflaging. The findings broaden the understanding of identity work among girls with ADHD through four analytical themes: adjusting and suppressing behavior, navigating emotions and stereotypes, struggles in the school context, and the impact of medication. The results highlighted how participants struggled to conform to the roles expected by society, particularly within the school system. In their identity work, they also navigated the emotions that arose when confronted with the school’s idealized role model of a “female student.” Stereotypical thinking further extended to perceptions of the ADHD diagnosis. The school system played a significant role in shaping identities and influencing the participants’ experiences and self-perceptions. This process was reported to be both demanding and challenging. Schools often initiated the ADHD assessments. Following diagnosis, medication was prescribed, which, while offering some benefits from an educational perspective, also came at a cost. The price to be paid was an identity transformation—becoming someone other than who they truly were. This process infused their identity work with reflections on who they really were versus who they were expected to be in a society that places high value on academic achievement and performance. From a Swedish ADHD perspective, social factors—such as roles, norms, standards, and ideals—must be considered in relation to the rising number of diagnoses. There may be a tendency to quickly seek medical explanations for deviant behavior, particularly in school settings, which can profoundly impact identity work, especially for girls on the ADHD spectrum. Some solutions may lie beyond the medical approach and instead be sought in organizational, pedagogical, and resource-based changes. Considerably more research is needed on the understudied group of girls with ADHD to better understand their identity work and the role of both society and schools in the increasing prevalence of diagnoses.